Content of Angiogenesis Markers of Insulin-Like Growth Factor-1 and Endostatin in Patients with Acute Myocardial Infarction in the Presence or Absence of Comorbid Obesity - Martovytskyi D.; Shelest O.; Kravchun P. (Львівський клінічний вісник)
Introduction. The study of markers which would improve the stratification of risk and diagnosis of acute myocardial infarction, is of great importance. The aim of the study. To investigate the content of angiogenesis markers insulin-like growth factor-1 and endostatin in patients with acute myocardial infarction in the presence or absence of comorbid obesity. Materials and methods. The study involved 46 patients with acute myocardial infarction with concomitant obesity who were treated in the infarctional department of the Kharkiv City Clinical Hospital (average age 62.1 ± 6.9 years). 22 of them with acute myocardial infarction with comorbidant obesity and 24 patients ‒ acute myocardial infarction without obesity. The groups were comparable by sex and age. The control group consisted of 20 healthy persons of corresponding age and sex. Аcute myocardial infarction was diagnosed according to ESC Guidelines for the management of acute myocardial infarction in patients presenting with ST-segment elevation, 2017. Obesity was diagnosed according to American association of clinical endocrinologists and American college of endocrinology clinical practice guidelines for comprehensive medical care of patients with obesity, 2016. The obesity was established by body mass index: 18.5 to 24.9 kg/m2 (normal weight) and 30.0 kg/m2 (obese). Results. In patients with acute myocardial infarction with obesity, the level of insulin-like growth factor was statistically significantly higher (p <0.05) than in the control group. The level of insulin-like growth factor-1 in acute obesity myocardial infarction (180.64 ± 12.2 ng/ml, p < 0.05) was statistically significantly higher than in the serum of patients with acute myocardial infarction without obesity (128.76 ± 8.10 ng/ml, p < 0.05). Positive correlations were revealed between the level of insulin-like growth factor-1 and body mass index (r = 0.27, p < 0.05), troponin I (r = 0.36, p < 0.05), and the thickness of the interventricular septum (r = 0,44, p < 0.05). There were negative correlations between the level of insulin-like growth factor-1 and the final diastolic size (r = -0.21, p < 0.05), the final systolic size (r = -0.22, p < 0.05), and the final systolic volume (r = -0.24, p < 0.05) and the final diastolic volume (r = -0.25, p < 0.05). Levels of enstostatin in the group of patients for acute myocardial infarction and obesity were lower than in the group of patients for acute myocardial infarction without obesity (148.26 ± 6.04 pmol/L and 169.83 ± 8.39 pmol/L, respectively, p < 0.05). Patients with obesity and without obesity with acute myocardial infarction showed higher levels of endostatin than the control (p < 0.05). Also, a positive correlation between the indices of endostatin and cardiohemodynamics was found. Conclusions. In patients with acute myocardial infarction, the activity of both markers of angiogenesis: insulin-like growth factor-1 and endostatin increases in comparison with healthy individuals in the control group. The presence of comorbid obesity is accompanied by a significant increase in the content of markers of angiogenesis due to insulin-like growth factor-1. The high activity of insulin-like growth factor-1 is accompanied by an increase in the content of proatherogenic lipids, together with a decrease in the volume and thickness of the wall of the left ventricle in patients with acute myocardial infarction and obesity. There was a negative correlation between the level of insulin-like growth factor-1 and echocardiographic parameters and, on the contrary, a positive correlation between the level of endostatin and echocardiographic indicators.